Identification of DNA polymorphism among clones of Hevea brasiliensis muell. arg. using RAPD analysis - Venkatachalam P; Gireesh T; Priya P; Saraswathyamma C K; Thanseem I; Thomas S; Thulaseedharan A (Indian Journal of Natural Rubber Research, 2002)
RAPD (Random amplified polymorphic DNAs) were used to study the DNA polymorphism in 37 Hevea clones representing variability for several morphological, physiological and other characters. Eighty random sequenced 10-mer primers were useed of which nine produced clear and scorable bands while eight produced polymorphic amplification products between 300 to 4000 base pairs in size, sufficient to distinguish between the clones. Of bands from the 8 primers 51.5;were polymorphic in the Hevea clones studied. A dendrogram developed using Jaccard's coefficients indicated genetic relationships among these clones. Most of the primary clones were clustered together in the dendrogram. UPGMA cluster analysis indicated that some of the clones are genetically close although they have been developed from different breeding programmes. The presence of polymorphic bands in the genomic DNA was further confirmed by Southern blot analysis. Detection of DNA polymorphism in the Hevea clones opens up the possibility of development of molecular map. This molecular approach will be useful for developing marker-assisted selection tools for genetic improvement of Hevea.
Keywords: DNA polymorphism; DNA polymorphism; Hevea brasiliensis; Hevea brasiliensis; Random oligonucleotide; Random oligonucleotide; RAPD; RAPD